A Case Report of Isotretinoin: Acute Eosinophilic Pneumonia, A Rare Adverse Reaction - Kadir Küçük (Wolters Kluwer Medknow Publications, 2024)
This is a case of acute eosinophilic pneumonia (AEP) in a 21-year-old woman with acne vulgaris who was treated with isotretinoin. During treatment, her blood tests showed normal results until the third month, when there was a slight increase in eosinophil count. In the fifth month of treatment, the patient presented to the pulmonology outpatient clinic with complaints of shortness of breath. Lung CT imaging revealed infiltration in both lungs characterized by ground glass opacities. AEP was diagnosed based on blood and imaging results. Isotretinoin therapy was terminated, and oral steroids were initiated, resulting in the improvement of the patient's symptoms. The patient had no additional risk factors except for smoking, but she had not started or resumed smoking after quitting. This case report highlights the possibility of hypersensitivity pneumonitis following isotretinoin administration.